Effects of preparation temperature on the conductivity of polypyrrole conducting polymer - Kassim, Anuar; Basar, Zarina; Mahmud, H.N.M. Ekramul (Indian Academy of Sciences, 2002)
An attempt has been made to investigate the effect of temperature on the conductivity of polypyrrole conducting polymer films prepared by an electrochemical method in an aqueous medium using camphor sulfonate as the dopant. The polymer was grown from aqueous solutions employing a range of temperatures (1-60°C). It was found that with increase in temperature the conductivity decreased and the optimum temperature was found to be between 10 and 30°C. The results show that the polymer formed at low temperature has higher conductivity and is stronger than that formed at higher temperatures. Characterization by X-ray scattering shows that interlayer distance, dBragg (Å), increases with increasing temperature. The morphology of the films formed was studied by using a scanning electron microscope (SEM). The changes in conductivity and physical appearance were interpreted as being due to compactness in the molecular packing and formation of αβ linkages in the film.